MEMBUMIKAN METODE PALS PADA DIGITALISASI PENGELOLAAN DASAR KEUANGAN FORUM UMKM MRANGGEN DEMAK - Santoso, Aprih; Saifudin, Saifudin; Sulistyawati, Ardiani Ika (Universitas YPPI Rembang, 2025)
Current conditions based on a pre-survey by the Community Service Team, many members of Mranggen District MSME Actors are unable to manage their MSME finances properly, especially in managing income and expenses and separating personal finances from business finances. On the one hand, reduced income due to the global food crisis has an impact on irregular income for MSMEs. On the other hand, increased expenses, due to the needs and prices of consumer goods also make it difficult to manage MSME finances. This is what motivated the Community Service Team to be interested in carrying out community service for members of Mranggen District MSME Actors. The Community Service Method with Introductory Training on financial management literacy integrated with digital finance and Mentoring. The results of the Community Service, MSME actors understand and are able to manage MSME finances integrated with digital finance neatly and well